Reasons for not/choosing chemistry: Why advanced level chemistry students in England do/not pursue chemistry undergraduate degrees. Issue 5 (10th October 2022) - Archer, Louise; Francis, Becky; Moote, Julie; Watson, Emma; Henderson, Morag; Holmegaard, Henriette; MacLeod, Emily
Abstract: There are international concerns about decreasing rates of chemistry degree enrolment. This article seeks to understand students' reasons for not/choosing to pursue a chemistry degree, drawing on (i) open‐ended survey responses from a sample of 506 students in England aged 21–22 who had studied advanced level ("A level") chemistry at age 18 (as either a full A level or a half "AS" level) and had either chosen ( n  = 70) or not chosen ( n  = 436) to pursue undergraduate chemistry and (ii) 185 interviews conducted with a subsample of 18 young people who had been longitudinally tracked from age 10 to 22 (with 17 of their parents) who took advanced level chemistry and then either did ( n  = 5), or did not ( n  = 13) go on to study for a chemistry degree. Analysis revealed four key reasons for not/choosing chemistry that were present to varying extents in both the quantitative and qualitative data ( relative interest, connection and options; experiences of chemistry A level; feeling "not/clever enough"; and views of chemistry jobs ). Four additional factors were predominantly found in the qualitative data ( associations of chemistry with masculinity; encouragement from a significant adult; views of higher education; and chemistry work experience/outreach ). Applying a sociological lens, we suggest that not/choosing chemistry was a relational process, produced through interactions of habitus, capital, and field. We identify conceptual and methodological implications and extrapolate reasons why chemistry degree enrolments may be declining, offering suggestions for how chemistry education might further support participation.